Hypericin: Source, Determination, Separation, and Properties. Issue 1 (2nd January 2022) - Zhang, Jie; Gao, Ling; Hu, Jie; Wang, Chongjun; Hagedoorn, Peter-Leon; Li, Ning; Zhou, Xing
ABSTRACT: Hypericin is a naturally occurring compound synthesized by certain species of the genus Hypericum, with various pharmacological effects. It is used as a natural photosensitizing agent with great potential in photodynamic therapy. This review discusses the latest results about the biosynthetic pathways and chemical synthetic routes to obtain hypericin. Although many analysis methods can be used for the determination of hypericin purity, HPLC has become the method of choice due to its fast and sensitive analyses. The extraction and purification of hypericin are also described. Hypericin can be used as a photosensitizer due to a large and active π-electron conjugated system in its structure. Medical applications of hypericin are not easy due to several unsolved practical problems, which include hypericin phototoxicity, poor solubility in water, and extreme sensitivity to light, heat, and pH.